DIGITAL TRANSFORMATION OF EDUCATION: THE FATE OF PHILOSOPHY AS A DISCIPLINE OF THE HUMANITIES CYCLE - Sukhova, Nadiia (Proceedings of the National Aviation University Series Philosophy Cultural, 2025)
Higher education in the 21st century is undergoing a complex digital transformation, adapting to the demands of the Fourth Industrial Revolution. In Ukraine, consumerist ideology has redefined students as service recipients and teachers as providers, turning universities into non-commercial enterprises. As economic values eclipse ethical and cultural ones, education risks losing its humanistic mission. The marginalization of the humanities—especially philosophy—in technical curricula is especially concerning. As AI reshapes human consciousness, the erosion of critical thinking threatens the future. The aim of this study is to identify the key features of the digital transformation of education and to examine the role and fate of philosophy as a humanities discipline in the network society. Research methods combine general scientific and philosophical approaches to analyze shifts in consciousness, education, and ways of living. The comparative method helps contrast scholars’ forecasts on solving urgent challenges in education and related fields. Research results. The 21st century has brought profound transformations across all areas of human life. Digitalization, as a core feature of innovation, is reshaping reality by merging the physical and virtual into a cyber-physical space. Human activity increasingly shifts online, changing consciousness, behavior, and communication. Education, particularly in Ukraine, reflects these shifts: students are viewed as service recipients, while universities function under market logic. This leads to the commodification of education and marginalization of the humanities, especially philosophy. At the same time, digital tools demand new competencies from educators and reshape teaching practices. Philosophy gains renewed relevance in addressing ethical, existential, and cognitive challenges posed by the digital world. Issues like internet dependence, loss of autonomy, and the erosion of human connection reveal the urgent need for critical thinking and moral reflection. Therefore, reinforcing philosophy in education is essential to help society navigate the digital transition responsibly, preserving human dignity, creativity, and the capacity for ethical choice. Discussion. The digital age imposes a worldview shift that may activate a "self-destruction mechanism" of humanity as a biological species. As robotization expands into education and healthcare, humans risk becoming dependent on pre-programmed responses, losing intuition and the ability to take responsibility. This creates a kind of “Human Design” – a digitally shaped personality optimized to conform to virtual norms rather than question them. To avoid this trajectory, we must return to history and philosophy, which provide diverse approaches to crises and human-environment relations. Without ethical reflection, society risks losing critical thinking, moral autonomy, and even historical memory. Conclusions. The digital transformation of education, while advancing control and material efficiency, fails to foster the spiritual growth of the individual. As AI gains power, there is a risk of diminishing human volition and detachment from physical reality. This raises concerns about the preservation of core values such as will, love, and freedom. To prevent dehumanizing outcomes, the education system must strengthen its focus on the humanities. Excluding philosophy could accelerate dystopian trends, while cultivating critical thinking and emotional intelligence remains key to a balanced digital future